Energy sprawl solutions : balancing global development and conservation - Kiesecker, Joseph M.; Baruch-Mordo, Sharon; Baumgarten, Leandro; Cameron, David R.; Cardenas Lopez, Juan J.; Crane, Laura; Evans, Jeffrey S.; Fargione, Joseph; Naugle, David E. (Island Press, 2017)
Over the next several decades, as human populations grow and developing countries become more affluent, the demand for energy will soar. Parts of the energy sector are preparing to meet this demand by increasing renewable energy production, which is necessary to combat climate change. But many renewable energy sources have a large energy sprawl--the amount of land needed to produce energy--which can threaten biodiversity and conservation. Is it possible to meet this rise in energy demand, while still conserving natural places and species? The editors provide a roadmap for preserving biodiversity despite the threats of energy sprawl. Their strategy--development by design--brings together companies, communities, and governments to craft blueprints for sustainable land development. This commonsense approach identifies and preemptively sets aside land where biodiversity can thrive while consolidating development in areas with lower biodiversity value. This approach makes sense for energy industries and governments, which can confidently build sustainability into their energy futures. This contributed volume brings together experts in diverse fields such as biodiversity conservation, ecology, ecosystem services, wildlife, fisheries, planning, energy, economics, and finance. Early chapters set the context for global patterns of biodiversity risk from energy extraction and the challenges of achieving a green future while maintaining energy security. Middle chapters are devoted to case studies from countries around the world, each describing a different energy sector and the collaborative process involved in planning complex energy projects in a way that maximizes biodiversity protection. Detailed maps and charts help orient readers to countries and energy sectors, providing proof for what is possible. With biodiversity declining rapidly because of an energy-hungry world, this book provides a needed guide for elected officials, industry representatives, NGOs and community groups who have a stake in sustainable energy-development planning.- Resumé vydavatel